A parallel numerical computation of nucleon scattering from nuclei, including full spin coupling and coulomb forces - Mefford, Tim (2012)
The microscopic, momentum space, optical potential description of spin 1/2 x 1/2 scattering is extended to include the coupling of the singlet-triplet spin channels and the exact handling of the Coulomb force. Computing performance in constructing the optical potential and in solving the coupled-channels Lippmann-Schwinger equations is enhanced by parallelization via the PVM library. Cross sections and spin observables are predicted for p - C and p - He elastic scattering at 500 MeV. The complete set of nucleon-trinucleon reactions is calculated to investigate the sensitivity of these reactions to charge-symmetry breaking effects. === Graduation date: 1996